Impact of implementation of PSAK 73 on leases: relevance of financial statements, financial performance and tax avoidance - Purwitasari, Ribka Lotty; Kuntadi, Cris (Gema Wiralodra, 2023)
The accounting treatment for leases has changed with the issuance of PSAK 73 which became effective on January 1, 2020. PSAK 73 is a new accounting standard that adopts the old IFRS 16 policy and regulates how an asset is recognized, measured, presented and disclosed in Financial Statements. The standard will have significant changes to the recognition of lease accounting which will be disclosed in the financial statements. This literature study article is based on previous research or research that is relevant to reviewing the impact of applying PSAK 73 on leases on the relevance of financial statements, financial performance and tax avoidance. The purpose of writing this literature study is to build a hypothesis from the application of PSAK 73 on leases to be used for further research. The method used in writing this article is the library research method which originates from online media including Google Scholar, Mendeley and other academic online media. the right company, 2) the impact of the application of PSAK 73 on financial performance on asset capitalization which resulted in significant changes in the Financial Statements, and 3) the impact of the application of PSAK 73 on tax avoidance in the implementation of tax rules on leases, especially in fiscal corrections and income tax calculations.